Reinventare la finzione: Lejos de Roma di Pablo Montoya (Altre Modernità, 2019)
Reinventare la finzione: Lejos de Roma di Pablo Montoya (Bogotá, Alfaguara, 2008, 178 pp. ISBN 978-958-704-694-6)di Alessandro Secomandi